Human nature, communication and trust - Putterman, Louis (2009)
The facts that people can sometimes commit to fulfill promises even when there are no binding penalties and that kind and trusting acts are often reciprocated by trust-worthy ones make possible forms of group action that might be ruled out in a hypothetical world of perfectly opportunistic individuals. I discuss some new experiments with a modified Berg. Dickhaut and McCabe (1995) `trust game' that provide evidence that most subjects adhere to non-binding agreements, that many are prepared to rely on trust rather than use binding but moderately costly contracts, that the possibility of exchanging words rather than mere numerical proposals enhances trusting and trustworthiness, and that subjects are drawn to fa ir and efficient exchanges despite the self-interest model's prediction of outcomes more favorable to first-movers. - Reproduced.
Keywords: Human species